Kajian Karakteristik Profil Pantai Dengan Menggunakan Metode Equilibrium Beach Profile Di Kecamatan Sinaboi Kabupaten Rokan Hilir - Erwin Satria Anugrah; Rinaldi Rinaldi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Coastal area is a very vulnerable to changes, because dynamic movement which are cause by the wave. A wave move bring a very easy basic particle coast and make errotion andaccresion in some area of coast. But, a coast will be return into a basic form if they had a balance character. Equilibrium Beach Profile (EBP) method is empirical correlation a scale parameter and the sediment size or fall velocity allow computation z = Ax2/3. Thismethod first time applicated by Robert G Dean in the beach California, United States. A purpose of research is want to know a balance of the coast in Sinaboi, Rokan Hilir with Equilibrium Beach Profile method. From analysis cross section data in some area, a slope formed by Equilibrium Beach Profile method almost approaching existing slope. A some cross section data which has a difference with existing slope and then justified a parameter.Keyword: coast, slope, equilibrium beach profile, coast change.